THE EFFECT OF ONLINE LEARNING USING ONLINE MEDIA ON LEARNING ACHIEVEMENT - Dona Fitriawan (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2022)
The purpose of this study was to determine the effect of online learning using online media on learning achievement. This type of research uses quantitative descriptive methods and the subjects of this research are 4th semester students at STKIP Kumala Lampung Metro which is conducted online. In this study, the online media used included applications such as Google Classroom, WhatsApp and YouTube. The results of this study indicate that the t-count value for online media is 4.012 with a significance level of 0.001, the online media variable has a positive and significant effect on the t-count value (4.012) > t table (2.101) and significant value (0.001) <0.05 . So it can be concluded that there is a significant influence between online media variables (X) on learning achievement (Y)